Fermi-surface traversal resonance in alpha-(BEDT-TTF)(2)KHg(SCN)(4) - Ardavan, A; Schrama, J; Semeno, A; Blundell, S; Singleton, J; Goy, P; Kurmoo, M; Day, P (Elsevier, 1999)
We experimentally demonstrate a mechanism for a new kind of magnetic resonance, the Fermi-surface traversal resonance (FTR). This is caused by the periodic traversal of carriers across quasi-one-dimensional (Q1D) sections of Fermi surface (FS) in an external magnetic field. Owing to the warping of the Q1D Fermi sheets, the real space velocities of the carriers oscillate as they cross the FS, generating resonances in the high frequency conductivity of the material. The results contain information about the FS, including the direction and harmonic content of the warping components. Using a rotating resonant-cavity system, FTRs have been observed in alpha-(BEDT-TTF)(2)KHg(SCN)(4).